The ethics of psychoactive ads - Hyman, Michael R. (Journal of business ethics, 1990)
Many of today's ads work by arousing the viewer's emotions. Although emotion-arousing ads are widely used and are commonly thought to be effective, their careless use produces a side-effect: the psychoactive ad. A psychoactive ad is any emotion-arousing ad that can cause a meaningful, well-defined group of viewers to feel extremely anxious, to feel hostile toward others, or to feel a loss of self-esteem. We argue that, because some ill-conceived psychoactive ads can cause harm, ethical issues must arise during their production. Current pretesting methods cannot identify the potentially psychoactive ads; therefore, we offer some tentative guidelines for reducing the number of viewers harmed by psychoactive ads.